Synthesis and antileishmanial evaluation of thiazole orange analogs. Issue 1 (1st January 2020) - Abdelhameed, Ahmed; Liao, Xiaoping; McElroy, Craig A.; Joice, April C.; Rakotondraibe, Liva; Li, Junan; Slebodnick, Carla; Guo, Pu; Wilson, W. David; Werbovetz, Karl A.
Graphical abstract: Abstract: Cyanine compounds have previously shown excellent in vitro and promising in vivo antileishmanial efficacy, but the potential toxicity of these agents is a concern. A series of 22 analogs of thiazole orange (( Z )-1-methyl-4-((3-methylbenzo[ d ]thiazol-2(3 H )-ylidene)methyl)quinolin-1-ium salt), a commercial cyanine dye with antileishmanial activity, were synthesized in an effort to increase the selectivity of such compounds while maintaining efficacy. Cyanines possessing substitutions on the quinolinium ring system displayed potency against Leishmania donovani axenic amastigotes that differed little from the parent compound (IC50 12–42 nM), while ring disjunction analogs were both less potent and less toxic. Changes in DNA melting temperature were modest when synthetic oligonucleotides were incubated with selected analogs (ΔTm ≤ 5 °C), with ring disjunction analogs showing the least effect on this parameter. Despite the high antileishmanial potency of the target compounds, their toxicity and relatively flat SAR suggests that further information regarding the target(s) of these molecules is needed to aid their development as antileishmanials.